Pengembangan LKPD Kontekstual Berbantuan Zep Quiz Untuk Meningkatkan Kemampuan Literasi Matematis dan Motivasi Belajar - Trisnavia, Vivi; Imswatama, Aritsya; Lukman, Hamidah Suryani (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2026)
The purpose of the development of the Contextual Learning Activity Sheet (LKPD) with Zep Quiz is to improve mathematical literacy and learning motivation. The research subject is eighth grade students at SMP PGRI Caringin, with the subject of study being statistics. The research method used was Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Data collection techniques used include interviews, expert validation, survey distribution, testing, and documentation. The results of this study are as follows: (1) The expert validation was performed by the subject matter and media experts. The expert content validation received a score of 91%, while the expert media validation received a score of 94%, both of which are considered